Epidemiology of Hepatocellular Carcinoma in the Asia-Pacific Region - Zhu, Ran Xu; Seto, Wai-Kay; Lai, Ching-Lung; Yuen, Man-Fung (Gut and liver, 2016)
Hepatocellular carcinoma (HCC) is the predominant primary liver cancer in many countries and is the third most common cause of cancer-related death in the Asia-Pacific region. The incidence of HCC is higher in men and in those over 40 years old. In the Asia-Pacific region, chronic hepatitis B virus and hepatitis C virus infections are the main etiological agents; in particular, chronic hepatitis B infection (CHB) is still the major cause in all Asia-Pacific countries except for Japan. Over the past two decades, the incidence of HCC has remained stable in countries in the region except for Singapore and Hong Kong, where the incidence for both sexes is currently decreasing. Chronic hepatitis C infection (CHC) is an important cause of HCC in Japan, representing 70% of HCCs. Over the past several decades, the prevalence of CHC has been increasing in many Asia-Pacific countries, including Australia, New Zealand, and India. Despite advancements in treatment, HCC is still an important health problem because of the associated substantial mortality. An effective surveillance program could offer early diagnosis and hence better treatment options. Antiviral treatment for both CHB and CHC is effective in reducing the incidence of HCC.